A comparative analysis of voluntary risk disclosures - Probohudono, Agung Nur (Curtin University, 2012)
This thesis examines voluntary risk disclosures from 600 firm year annual reports in four countries’ (Australia, Indonesia, Malaysia, and Singapore) manufacturing listed companies for the 2007-2009 financial years. This is an important time span to investigate risk disclosures as it encompasses those years most directly impacted by the Global Financial Crisis (GFC). Longitudinal and cross country analyses test the veracity of agency theory to predict the level of firms’ risk disclosures. A comprehensive risk disclosure index (RDI) checklist is created and tested to explain the extent of such communication over time. T-tests, ANOVA, correlations and regression analysis are used for the statistical testing.The findings show that overall RDI scores over the economically-challenging GFC time period is relative low averaging 33.73%. The RDI rises every year ranging from 31.46% in 2007, 34.20% in 2008, and 35.54% in 2009. There is a vast disparity of communication across the various risk elements. The RDI item “Identifying, evaluating and managing significant risks” has the highest level of communication (91.17%), while “Effects of inflation on assets quantitative’’ is the lowest RDI item with no disclosure (0 %). The highest major sub-category for RDI is business risk (46.55%) while the strategy risk category (17.21%) is the lowest communicated.Multiple regression analysis provides evidence that size, managerial ownership, board independence, and profitability are positively associated with the extent of voluntary risk disclosure. There are also clear country differences, for instance, Indonesian companies have statistically lower levels of risk disclosure compared with Malaysia. These findings are useful for self-evaluation and benchmarking of risk communication by other corporations across the global landscape. The need for mandatory regulation regarding key risks elements is advanced. Overall, varying levels of risk disclosure over time and across countries are influenced by key firm characteristics and economic drivers consistent with agency theory tenets.